"So Shines a Good Deed in a Weary World": Intertextuality in Steven Spielberg's Ready Player One (2018). - Metz, Walter (Film Criticism, 2018)
The article focuses on intersexuality in the film "Ready Player One," directed by Steven Spielberg. The author compares Speilberg to film director George Lucas, discusses the culture of the 1980s used within the film "Ready Player One," and explores its relation to "The Shining," directed by Stanley Kubrick.